Positive relationship between odor identification and affective responses of negatively valenced odors - Martinec Nováková, Lenka; Plotěná, Dagmar; Roberts, S. Craig; Havlíček, Jan (Frontiers in Psychology, 2015)
Hedonic ratings of odors and olfactory preferences are influenced by a number of modulating factors, such as prior experience and knowledge about an odor’s identity. The present study addresses the relationship between knowledge about an odor’s identity due to prior experience, assessed by means of a test of cued odor identification, and odor pleasantness ratings in children who exhibit ongoing olfactory learning. Ninety-one children aged 8-11 years rated the pleasantness of odors in the Sniffin’ Sticks set and, subsequently, took the odor identification test. A positive association between odor identification and pleasantness was found for two unpleasant food odors (garlic and fish): higher pleasantness ratings were exhibited by those participants who correctly identified these odors compared to those who failed to correctly identify them. However, we did not find a similar effect for any of the more pleasant odors. The results of this study suggest that pleasantness ratings of some odors may be modulated by the knowledge of their identity due to prior experience and that this relationship might be more evident to unpleasant odors.